Rare genetic interstitial lung diseases: a pictorial essay - Raphael Borie; Laureline Berteloot; Caroline Kannengiesser; Matthias Griese; Aurelie Cazes; Bruno Crestani; Alice Hadchouel; Marie Pierre Debray (European Respiratory Review)
The main monogenic causes of pulmonary fibrosis in adults are mutations in telomere-related genes. These mutations may be associated with extrapulmonary signs (hepatic, haematological and dermatological) and typically present radiologically as usual interstitial pneumonia or unclassifiable fibrosis. In children, the monogenic causes of pulmonary fibrosis are dominated by mutations in surfactant-related genes. These mutations are not associated with extrapulmonary signs and often manifest radiologically as unclassifiable fibrosis with cysts that can lead to chest wall deformities in adults. This review discusses these mutations, along with most of the monogenic causes of interstitial lung disease, including interferon-related genes, mutations in genes causing cystic lung disease, Hermansky–Pudlak syndrome, pulmonary alveolar proteinosis, lysinuric protein intolerance and lysosomal storage disorders, and their pulmonary and extrapulmonary manifestations.